2021
DOI: 10.3390/ma14195787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Factors on Tensile Shear Load Using the Definitive Screening Design in Friction Stir Lap Welding of Aluminum–Steel with a Pipe Shape

Abstract: Recently, friction stir welding of dissimilar materials has emerged as one of the most significant issues in lightweight, eco-friendly bonding technology. In this study, we welded the torsion beam shaft—an automobile chassis component—with cast aluminum to lighten it. The study rapidly and economically investigated the effects of friction stir welding and process parameters for A357 cast aluminum and FB590 high-strength steel; 14 decomposition experiments were conducted using a definitive screening design that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“… Overall configuration diagram of FSW experiment. ( a ) tool and close view of shoulder; ( b ) photograph of experimental equipment; and ( c ) tool penetration depth (TPD) [ 16 ]. …”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“… Overall configuration diagram of FSW experiment. ( a ) tool and close view of shoulder; ( b ) photograph of experimental equipment; and ( c ) tool penetration depth (TPD) [ 16 ]. …”
Section: Figurementioning
confidence: 99%
“…In the aerospace and automotive industries, the alloys A356 and A357 are widely used for casting high-strength parts because they provide a combination of high strength while having good casting properties [ 10 , 11 , 12 , 13 ]. The FSW of A357 and FB 590 was studied to reduce the weight of automobile parts [ 14 , 15 , 16 ]. Park et al [ 14 ] reported that by performing dissimilar FSW of 3 mm thick A357 cast Al and FB590 HSS plate, a tensile shear load (TSL) of 72.8% was achieved compared to the Al base material with TSL of 7912 N. The FSW process is mainly divided into four phases, and the normal force is changed in them [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations